Methods of Analysizing New Words by Reading Texts - Nasretdinova, Mukhlisa Nizometdinovna; Ruxshona, Xamidova (PT. Antis International Publisher, 2024)
As a language learner, you work hard to expand your vocabulary. You plough through new words every day, make long lists of words and practise with flashcards. However, when it comes to speaking, the new words seem to fall out of your head, so you resort to your old friends – words you already know and have used many times – again and again. Remembering and using new words in speech is often a challenge for language learners. This article goes on to think about word memorization and its methods.